Social and National Composition of the Communists of Lithuania from the end of 1939 to September 1940 - Maslauskienė, Nijolė (Genocidas ir rezistencija, 2025)
The Communist Party of Lithuania (CPL), an illegal and anti-State party in pre-war Lithuania, was modelled on All Union Communist(b) Party VKP(b) and served the interests of the Soviets prior to and after the occupation. Pursuing to preserve its social and ideological integrity, the CPL exercised the policy of control over its composition. Strict membership and admittance rules, fixed membership limits for definite social groups and a consistent socio-political purges of party ranks were the basic methods regulating the party’s composition. The national composition of the CPL had its specifics too. Owning to the fact that many Lithuanian people disapproved of the illegal activities of the party, their membership in it did not match the membership of the country’s ethnic minorities. Thus, the CPL’s national composition in 1939 was as follows: up to 60%–Lithuanians, 31%–Jews, and 9%–other minorities. In Kaunas, the temporary capital of pre–war Lithuania, of all the communists 70.88% were Jews. The predominance of Jews in CPL ranks accounts for their domination among craftsmen, tradesmen and poor residents of cities as well as for their anti-Zionist and pro-Soviet attitudes at the outbreak of World War II. After the Soviet occupation the CPL became an instrument of the invaders in installing the Soviet regime. A new historic situation demanded of the party to be reorganised and subsequently its aims to be revised. The implant of the Soviet totalitarian regime in collaboration with Soviet invaders became the main task of the party. In order to concentrate the power in its hands in a short span of time, the CPL was quick to expand its ranks. From June to October 1940, the number of communist jumped 4.25 times. However, the concern that petty–bourgeois elements and Jews, according to the Bolsheviks, prevailed among the new members made the party slacken the growth of its ranks and regulate its social composition. The method of selection lowered the number of craftsmen, tradesmen and the like in the CPL’s ranks.